Metafísica y bioética II: problemas bioéticos: Acerca de Antropología y problemas bioéticos de R. Lucas Lucas - Villagrasa, L.C., Jesús (Alpha Omega, 2002)
Summary: In his previous article the author had examined the epistemologica! foundations of Bioethics. In the present, real metaphysical principi es of Bioethics are founded upon an analysis of significant bioethical problems. These principles are sought in F. Lucas Lucas’ book "Anthropologia y problemas bioéticos ". This book is an analysis of bioethical questions from the perspective of an anthropology solid rooted in metaphysics. The article concludes by indicating various tasks thai Metaphysics musi develop lo arrive al a solid foundation of Bioethics.